Bankruptcy law and angel investors around the world - Cumming, Douglas; Zhang, Minjie (Journal of International Business Studies, 2023)
We conjecture that angel investment in entrepreneurial firms depends on two types of bankruptcy laws around the world. Corporate bankruptcy laws impact investor terms and incentives to finance risky entrepreneurs, particularly given reforms that brought about a time-efficient, simplified, and clear process in recent years in some countries. Personal bankruptcy laws impact entrepreneurial motivations to engage in risk-taking and entrepreneurship and thus affect the demand for angel financing. In this paper, we examine 35,752 angel investments from 72 countries from 2000 to 2020 and compare the relative importance of corporate and personal bankruptcy laws for angel investment activities. The data indicate that corporate bankruptcy law reforms and personal bankruptcy law reforms both positively influence angel investment activities. The data further suggest that countries that reformed both laws had the most pronounced improvements in angel activities. These findings are robust using a quasi-experimental approach of the difference-in-differences method, clustering standard errors, and excluding U.S. observations, among other strategies.